PERLINDUNGAN TERHADAP MASYARAKAT DALAM KAITANNYA DENGAN PENYIARAN YANG DILAKUKAN OLEH LEMBAGA PENYIARAN BERBASIS INTERNET - Cyntia Estevania; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
Broadcasting in Indonesia is not only carried out by conventional broadcasters in the form of television and radio, but also by Youtube and Netflix, which are internet-based broadcasting institutions. The refusal of the RCTI application by the Constitutional Court through Decision Number 39/PUU-XVIII/2020, and the non-binding of internet-based broadcasting institutions to the provisions contained in the Broadcasting Law have bad consequences for Indonesia's young generation. The purpose of this study is to determine the regulation of broadcasting in Indonesia, and the protection of the public in relation to broadcasting by internet-based broadcasting institutions. The research method used is descriptive normative law and a law approach. Based on the results of the analysis, broadcasting in Indonesia must be based on Pancasila and the 1945 Constitution of the Republic of Indonesia with the principles, objectives, functions, and directions of broadcasting regulated in the Broadcasting Law. From this research, there is no protection for the viewers of internet-based broadcasting institutions. It is recommended that the government make changes to Law Number 32 of 2002 concerning Broadcasting so that there are regulations on broadcasting carried out by internet-based broadcasting institutions, and the public who view broadcasts of internet-based broadcasting institutions receive legal protection.